Cover Image, Volume 58, Issue 8. Issue 8 (26th August 2020) - Syal, Sapna; Ng, Chris; Kim, Yunah; Janbieh, Javier; Govind, Shubha; Deshpande, Girish
Abstract : Cover illustration : The cover image is based on the Original Article Reactive Oxygen Species (ROS) Signaling in Primordial Germ Cell Development in Drosophila embryos, by Girish Deshpande et al., https://doi.org/10.1002/dvg.23362 .